Morphology, composition, structure and optical properties of thermally annealed Cu2O thin films prepared by reactive DC sputtering method. (2nd September 2018) - Wisz, G.; Sawicka-Chudy, P.; Potera, P.; Sibiński, M.; Yavorskyi, R.; Głowa, Ł.; Cieniek, B.; Cholewa, M.
Abstract: Thin films copper oxides are perspective materials for many optoelectronic applications, including photovoltaics. The samples were deposited on glass and silicon substrates by magnetron sputtering method using Modular Platform PREVAC. After deposition the samples were thermally treated by annealing in oxygen atmosphere for 60 min at 450 °C. Morphology confirms that all the films have crystalline structure. Optical measurements show that the films have wide band gap within the range 2.20÷ 2.48 eV before and 2.03÷ 2.40 eV after annealing. The article presents the discussion about the influence of annealing on Cu2 O thin film parameters. Graphical Abstract: